Assessing the Use of ICT in Teaching and Learning a Foreign Language in Rwandan Schools: An Example of English in Selected Secondary Schools of Rusizi District - Donard Bikorimana; Prosper Murwanashyaka (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Information Communication and Technology (ICT) is viewed as a tool to make life easier by affecting every aspect of human life. In the field of education, teaching and learning of a foreign language has also been greatly affected. This This study was guided by the following specific objectives: to identify the contribution of ICT in the teaching and learning of a foreign language in selected secondary schools in Rusizi District-Rwanda, to analyse the disadvantages of the misuse of ICT in the teaching and learning of a foreign language and to determine how ICT can be used in the teaching and learning of a foreign language. Data was collected using literature review, observation, interview, and questionnaire. Data from literature review, observation and interview were analyzed and presented in a descriptive manner while data from questionnaire were analyzed and presented in graphs and percentages. The sample were 9 English teachers, 10 parents and 47 students of senior five LKK (Literature in English-Kiswahili and Kinyarwanda) combination from 4 selected schools in Rusizi District. This sample was obtained using the purposive sampling method. The study was guided by Connectivism Learning Theory. The results showed that ICT is an effective tool in teaching vocabulary, grammar, and the four language skills of a foreign language. However, teachers use ICT while teaching writing on 30% and reading on 29% while vocabulary took 22% and speaking 10%. Additionally, teachers and students often use YouTube 80% and seem to ignore other tools such as Meeting Conference Apps. This research has also revealed that if ICT is not used properly, it may harm the teaching and learning process. Therefore, we discussed how ICT should be used in the teaching and learning of a foreign language in Rwanda.